Information professionals and copyright literacy: a multinational study. Issue 6 (15th August 2017) - Todorova, Tania Yordanova; Kurbanoglu, Serap; Boustany, Joumana; Dogan, Güleda; Saunders, Laura; Horvat, Aleksandra; Terra, Ana Lúcia; Landøy, Ane; Repanovici, Angela; Morrison, Chris; Vanderkast, Egbert J. Sanchez; Secker, Jane; et al.
Abstract : Purpose: The purpose of this paper is to present findings from a multinational survey on copyright literacy of specialists from libraries and other cultural institutions. Design/methodology/approach: This paper is based on a multinational survey of copyright literacy competencies of Library and Information Science (LIS) professionals and those who work in the cultural heritage sector (archives and museums), conducted in 13 countries, namely Bulgaria (BG), Croatia (CR), Finland (FI), France (FR), Hungary (HU), Lithuania (LT), Mexico (MX), Norway (NO), Portugal (PT), Romania (RO), Turkey (TR), UK and USA in the period July 2013-March 2015. An online survey instrument was developed in order to collect data from professionals regarding their familiarity with, knowledge and awareness of, and opinions on copyright-related issues. Findings: Findings of this study highlight gaps in existing knowledge of copyright, and information about the level of copyright literacy of LIS and cultural sector professionals. Also attitudes toward copyright learning content in academic education and continuing professional development training programs are investigated. Originality/value: This study aimed to address a gap in the literature by encompassing specialists from the cultural institutions in an international comparative context. The paper offers guidance for further understanding of copyright in a wider framework of digital and information literacy; and for the implementation of copyright policy, and the establishment of copyright advisor positions in cultural institutions. The recommendations support a revision of academic and continuing education programs learning curriculum and methods.